A review and analysis of the elasto-caloric effect for solid-state refrigeration devices: Challenges and opportunities. (21st December 2015) - Chauhan, Aditya; Patel, Satyanarayan; Vaish, Rahul; Bowen, Chris R.
ABSTRACT: This review article deals with the current state-of-art research and developments in the field of elasto-caloric effect as applicable for solid-state refrigeration devices. Furthermore, the current challenges and future prospects in the field of elasto-caloric refrigeration technology have also been discussed. Solid-state refrigeration is of interest since it has the potential to be a light-weight and environmentally-friendly alternative for small scale cooling. Much research is currently being undertaken to develop solid-state cooling technologies which is primarily achieved by utilizing the significant caloric effect exhibited by particular classes of materials. A variety of caloric effects exist including: electro-caloric, magneto-caloric, baro-caloric, and elasto-caloric. Among these, the elasto-caloric effect has shown potential within the field of mechanical refrigeration with shape-memory alloys being potential materials for producing significant levels of elasto-caloric cooling. This article explains the elasto-caloric effect in shape memory alloys, polymers, and ferroelectric materials. Technical parameters associated with the elasto-caloric performance of these materials are discussed. A discussion regarding existing functional shortcomings and future prospects in the field of mechanical refrigeration is covered. Aspects related to the long term environmental impact of solid-state cooling technology are also discussed. This study is aimed at promoting the understanding and commercial investigation of the elasto-caloric effect in the field of solid state refrigeration.